Status of One Health implementation in Botswana - Kgosimore, Moatlhodi; Mokhondo, N.; Pfukenyi, D.M.; Tlale, L.; Sebolai, B.; Segopolo, I.; Mmopi, K.; Ntshiamisang, K.; Tselaesele, N.M.; Baikitse, G.; Babayani, N.; Phokoje, S.; et al. (CAB International, 2024)
One Health (OH) is a collaborative, multisector and transdisciplinary approach to mitigate various issues related to the health of animals, plants, humans and ecosystems and their interactions for optimal health. In Botswana, the main goal of OH is to achieve resilient health outcomes that recognize the interrelationships between peoples, animals, plants and their shared environment. We conducted a desktop study, followed by key informants’ interviews (KII) and focus group discussions (FGD) in Botswana to define the current OH state of affairs as well as to identify education, training, research and policy gaps that need filling to facilitate effective implementation of OH in the country. The study results revealed that the country does not have an institutionalized nor legislated OH platform but rather intersectoral and multisectoral structures coordinated by the line ministries to address OH-related issues on an ad-hoc basis. Furthermore, it was found that institutions of higher learning in the country do not have deliberate OH programmes to spur traction of OH approaches but rather snippets of OH content infused in certain taught programmes. It is recommended from this study that there is an urgent need to adopt and adapt OH approaches in the country and institutionalize OH platforms for operational purposes through enaction and promulgation of relevant statutory instruments in the affected sectors of the economy, like health, education, environment and research.